Slips of the Tongue by Jokowi and Prabowo in the Presidential Debates 2019 - Rohi Qimmahtum; Bambang Yudi Cahyono; Achmad Effendi Kadarisman (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This current research, using a descriptive qualitative method, aims to find out and analyze the types of slip of the tongue produced by Jokowi and Prabowo during the presidential debates 2019. This current research applied the theories proposed by Altiparmak and Koruoglu (2014) to analyze types of slip of the tongue. The data were taken from video of the 2nd round presidential debate 2019, obtained from YouTube. The collected data were then transcribed and analyzed based on the types of slip of the tongue proposed by Altiparmark and Koruoglu (2014). There were 100 utterances of data found of slip of the tongue produced by Jokowi and Prabowo during the 2nd round of presidential debate 2019. Jokowi produced 60 slips of the tongue: deletions (46.67%), blends (21.67%), substitutions (11.67%), anticipations (11.67%), additions (5%), perseverations (1.66%), and misdeviations (1.66%). Prabowo produced 40 slips of the tongue: deletions (26.83%), substitutions (26.83%), anticipations (21.95%), additions (19.51%), blends (2.44%), and misdeviations (2.44%). The type of perseverations of slip of the tongue occurred in Jokowi’s utterances but did not occur in Prabowo’s utterances. Whereas, shifts and exchanges slip of the tongue are the two types that did not occur in their utterances. Keywords: slips of the tongue, Jokowi, Prabowo, presidential debates Abstrak: Penelitian ini menggunakan metode deskriptif kualitatif yang bertujuan untuk mengetahui dan menganalisa tipe-tipe selip lidah yang dihasilkan oleh Jokowi dan Prabowo selama debat presiden 2019. Penelitian ini menggunakan teori yang diajukan oleh Altiparmak dan Koruoglu (2014) untuk menganalisis tipe-tipe selip lidah. Data diambil dari video ronde kedua debat presiden 2019 yang diperoleh dari YouTube. Data yang terkumpul kemudian ditranskripsikan dan dianalisis berdasarkan pada tipe-tipe selip lidah yang diajukan oleh Altiparmak and Koruoglu (2014). Terdapat 100 data ucapan selip lidah yang ditemukan yang dihasilkan oleh Jokowi dan Prabowo selama ronde kedua debat presiden 2019. Jokowi memproduksi 60 kali selip lidah: deletions (46.67%), blends (21.67%), substitutions (11.67%), anticipations (11.67%), additions (5%), perseverations (1.66%), dan misdeviations (1.66%). Prabowo memproduksi 40 kali selip lidah: deletions (26.83%), substitutions (26.83%), anticipations (21.95%), additions (19.51%), blends (2.44%), dan misdeviations (2.44%). Perseverations adalah tipe kilir lidah yang terjadi pada ujaran Jokowi namun tidak terjadi pada ujaran Prabowo. Sedangkan shifts dan exchanges merupakan tipe selip lidah yang tidak terjadi dalam ujaran mereka. Kata kunci: selip lidah, Jokowi, Prabowo, debat pemilihan presiden